Foam cells and the pathogenesis of kidney disease. Issue 3 (May 2015) - Eom, Minseob; Hudkins, Kelly L.; Alpers, Charles E.
<x xml:space="preserve">Abstract</x> Purpose of review Foam cells in human glomeruli can be encountered in various renal diseases including focal segmental glomerulosclerosis and diabetic nephropathy. Although foam cells are key participants in atherosclerosis, surprisingly little is known about their pathogenicity in the kidney. We review our understanding (or lack thereof) of foam cells in the kidney, as well as insights gained in studies of foam cells and macrophages involved in atherosclerosis to suggest areas of investigation that will allow better characterization of the role of these cells in renal disease. Recent findings There is a general dearth of animal models of disease with renal foam cell accumulation, limiting progress in our understanding of the pathobiology of these cells. Recent genetic modifications of hyperlipidemic mice have resulted in some new disease models with renal foam cell accumulation. Recent studies have challenged older paradigms by findings that indicate that many tissue macrophages are derived from cells permanently residing in the tissue from birth rather than circulating monocytes. Summary Renal foam cells remain an enigma. Extrapolating from studies of atherosclerosis suggests that therapeutics targeting mitochondrial reactive oxygen species production, or modulating cholesterol and lipoprotein uptake or egress from these cells, may prove beneficial for kidney diseases in which foam cells are present.